2015
DOI: 10.1016/j.precisioneng.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

An in-process measurement method for repair of defective microstructures by using a fast tool servo with a force sensor

Abstract: a b s t r a c tThis paper presents an in-process measurement method, which is capable of conducting real-time position identification and on-machine profile characterization of micro-defects in defective microstructures by using a fast tool servo with a force sensor (FS-FTS) on an ultra-precision lathe. A real-time thrust force map is captured in the process of cutting the microstructures by the FS-FTS to indicate the cutting status with respect to the cutting tool position in the coordinate system of the lath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…22) [62]. Such measurement technology was also used for on-machine measurement of cutting edge contours of single point diamond tools [28] [25] and initial surface form of brittle workpieces [26] as well as for in-process measurement and repair of defective microstructures [29].…”
Section: Contact-type Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…22) [62]. Such measurement technology was also used for on-machine measurement of cutting edge contours of single point diamond tools [28] [25] and initial surface form of brittle workpieces [26] as well as for in-process measurement and repair of defective microstructures [29].…”
Section: Contact-type Probesmentioning
confidence: 99%
“…Feedback of the measured information to compensation machining of micro-structures is a challenging task due to the critical requirement on the positioning accuracy of the tool. Chen et al demonstrated the possibility of repairing defective microstructure elements on a large-area roll mould by using a FS-FTS [29]. The occurrence and the position of a defective element could be detected during the cutting process by the force sensor, and the sectional profile of the element could be characterized after the process, by using the tool itself as a force-controlled stylus probe.…”
Section: Feedback To Compensation Machiningmentioning
confidence: 99%
“…It can be a factor causing cutting tool deflection in milling process, a signal for tool wear monitoring or repairing the defection of machined surface [1] and so on. Many cutting force models based on orthogonal cutting have been proposed to predict the cutting force [2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…This new type of on-machine measurement technology has demonstrated its effectiveness in various applications of fabrications of the micro-structured surfaces. 8,1820…”
Section: Introductionmentioning
confidence: 99%
“…However, permanent contact marks with a depth of several nanometers have been confirmed in the previous research when the surfaces of soft metals such as copper and aluminum, which are the popular materials used in diamond cutting, are made to contact with the diamond tool in the current version of FS-FTS with a contact force measurement resolution of 0.06 mN and a tool displacement measurement resolution of 1 nm. 8,19…”
Section: Introductionmentioning
confidence: 99%